New Energy System in the Republic of Kazakhstan: Exploring the Possibility of Creating and Mechanisms of Implementing - Babazhanova, Zhanat; Khambar, Bakytgul; Yessenbekova, Assem; Sartanova, Nalima; Jandossova, Fatima (International Journal of Energy Economics and Policy, 2017)
The paper represents the analysis of modern data and information on the development of renewable energy sources and energy efficiency in the Republic of Kazakhstan. The purpose of this study is to identify trends in the development of alternative energy sources that are economically feasible at the current stage of the development of the energy complex and allow providing sustained growth in the national economy of the Republic of Kazakhstan. Analytical publications, interviews with experts, and other open sources of information were used as sources of secondary data. The conducted research allows formulating a number of conclusions. The Republic of Kazakhstan has a significant potential for the development of alternative energy. However, their share in total energy production remains rather low and the available capacities of the renewable energy sources (RES) facilities are not fully utilized. In the context of aggravation of global environmental problems, depletion of traditional types of energy and raw material resources, it has proved necessary to create a new energy system based on RES. The Government of the Republic of Kazakhstan needs to develop a long-term concept of rendering sustainable energy services. In addition, it is necessary to implement a set of measures to strengthen the enabling environment, including higher investments into renewable facilities. One of the most promising mechanisms for supporting the RES sector is the introduction of an auction system for selecting RES projects, which will help solve problems with planning and control of the budget to support RES. Keywords: energy efficiency, energy saving, GDP energy intensity, renewable energy sources (RES), alternative energy, solar energy, wind power, biofuels JEL Classifications: O13, Q42, Q43.